Tick Size, Competition for Liquidity Provision, and Price Discovery: Evidence from the U.S. Treasury Market - Fleming, Michael; Nguyen, Giang; Ruela, Francisco (Management Science, 2024)
This paper studies how a tick size change affects market quality, price discovery, and the competition for liquidity provision by dealers and high-frequency trading firms (HFTs) in the U.S. Treasury market. Using difference-in-differences regressions around the November 19, 2018, tick size reduction in the 2-year Treasury note and a similar change in the 2-year futures eight weeks later, we find significantly improved market quality. Moreover, dealers become more competitive in liquidity provision and price improvement, consistent with the hypothesis that HFTs find liquidity provision less profitable in the smaller tick size environment. Last, we find a significant shift in short-run price discovery toward the cash market, which then reverses when the futures market tick size is reduced, suggesting that the finer pricing grid in the cash market allows traders to act on small information signals that are not profitable to exploit in the larger-tick futures market. Our findings suggest that reducing the tick size in tick-constrained and highly liquid markets like the Treasury market is on balance beneficial. This paper was accepted by Bruno Biais, finance. Funding: F. Ruela acknowledges support from the National Science Foundation Graduate Research Fellowship Program [Grant DGE-1746045]. Any opinions, findings, and conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the National Science Foundation. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4663 .